2019
DOI: 10.1159/000496349
|View full text |Cite
|
Sign up to set email alerts
|

Can Iodixanol Prevent Post-Endoscopic Retrograde Cholangiopancreatography Pancreatitis? A Prospective, Randomized, Controlled Trial

Abstract: Background: It is yet not clear whether differences in the contrast medium may affect post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP). Aim: The aim of this study was to evaluate the rate of PEP between high osmolality contrast medium (HOCM) and iso osmolar medium (IOCM) in a prospective, randomized, controlled trial. Methods: Patients who were scheduled to undergo a diagnostic or therapeutic procedure under ERCP guidance were included. Patients were excluded from this study if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
8
0
5
Order By: Relevance
“…Ionic nature and osmolarity of the contrast media may cause chemical injury. 41 Operator-related factors are associated with the experience of the endoscopist. Endoscopists with less experience (<200 ERCP procedures) were an independent risk factor for the occurrence of PEP (odds ratio, 1.63).…”
Section: Discussionmentioning
confidence: 99%
“…Ionic nature and osmolarity of the contrast media may cause chemical injury. 41 Operator-related factors are associated with the experience of the endoscopist. Endoscopists with less experience (<200 ERCP procedures) were an independent risk factor for the occurrence of PEP (odds ratio, 1.63).…”
Section: Discussionmentioning
confidence: 99%
“…Contrast injection: It also has a cumulative risk for post-ERCP pancreatitis. A prospective, randomized, controlled trial found the use of the iso-osmolar medium (IOCM) associated with less severe post-ERCP pancreatitis than the usage of high osmolality contrast medium [14]. Thermal injury from electrosurgical devices contributes to the risk of post-ERCP pancreatitis [8,15].…”
Section: Procedure-related Risk Factorsmentioning
confidence: 99%
“…A prospective, randomized, controlled trial found the use of the iso-osmolar medium (IOCM) associated with less severe post-ERCP pancreatitis than the usage of high osmolality contrast medium. 14 Thermal injury from electrosurgical devices contributes to the risk of post-ERCP pancreatitis. 8,15 Intubation difficulty and operation time: Both of these act as independent risk factors for post-ERCP pancreatitis.…”
Section: Procedure-related Risk Factorsmentioning
confidence: 99%